Increased Growth of Caladium by Tuber Section and Plant Growth Regulators - Suriya Kosinwattana; Chamaiporn Anuwong (ASEAN Journal of Scientific and Technological Reports, 2023)
Caladium is a tuberous plant propagated by the tuber section technique to increase the plant quantity. Gibberellin (GA3) and indole-3-butyric acid (IBA) have great capability in various agricultural practices, such as growing rapidly and enlargement tuber size. The effects of different tuber section sizes and PGRs levels having the following constituents (GA3 and IBA) in different levels by 2x5 factorial in a completely randomized design (CRD) with ten replications. The treatments involved 2 factors: The first factor was separating two sizes of tuber section into a squall length of each size 0.5 and 1 cm, and the second factor was drenching the tuber in two different levels of each IBA (100 and 150 ppm) and GA3 (100 and 150 ppm). The results obtained from this experiment showed that the 1 cm of tuber section size was a higher significant difference in bud germination, tuber size, plant height, canopy width, and the number of leaves than the 0.5 cm of tuber section size. However, IBA at 150 ppm was a higher significant difference in the average survival rate, bud germination, plant height, canopy width, and the number of leaves than others. The interaction between the tuber size at 1 cm and IBA at 150 ppm gave the highest survival rate, bud germination, plant height, canopy width, and the number of leaves. Therefore, the Caladium was separated at 1 cm size and immersed in 150 ppm of IBA appropriated to induce growth after the section within two months.
Keywords: Flowering Plant Growth and Cultivation